Playing the odds in clinical decision making: lessons from berry aneurysms undetected by magnetic resonance angiography. Issue 7298 (2nd June 2001) - Johnson, Michael R; Good, Catriona D; Penny, William D; Barnes, Philip RJ; Scadding, John W
Abstract : The probability of a disease following a diagnostic test is critically reliant on prior clinical probability